2017
DOI: 10.1002/mmce.21224
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microwave ablation antenna optimization techniques

Abstract: Microwave ablation is a minimally invasive treatment modality for malignant and benign tumors in several organs. While many microwave ablation antennas have been described in the literature, most have been designed assuming normal ambient tissue and have not accounted for tissue property changes that occur during intense heating. We analyzed three optimization approaches for canonical monopole and dual‐slot antennas: minimal reflection, spherical specific absorption rate (SAR) pattern, and spherical ablation z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 41 publications
(102 reference statements)
1
24
0
Order By: Relevance
“…Previous studies have suggested that changes in dielectric properties can produce elongation of the electric field along the antenna, leading to elongation of the ablation zone itself . Other studies have attempted to create more spherical ablations through antenna design optimization . The present study demonstrated that for all powers and energy types, the primary direction of tissue contraction was orthogonal to this antenna design, with mean principal angles of −8.1º to 5.4º, dependent on the ablation powers and energy types (Fig.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Previous studies have suggested that changes in dielectric properties can produce elongation of the electric field along the antenna, leading to elongation of the ablation zone itself . Other studies have attempted to create more spherical ablations through antenna design optimization . The present study demonstrated that for all powers and energy types, the primary direction of tissue contraction was orthogonal to this antenna design, with mean principal angles of −8.1º to 5.4º, dependent on the ablation powers and energy types (Fig.…”
Section: Discussionsupporting
confidence: 53%
“…[34][35][36][37][38] Other studies have attempted to create more spherical ablations through antenna design optimization. [39][40][41] The present study demonstrated that for all powers and energy types, the primary direction of tissue contraction was orthogonal to this antenna design, with mean principal angles of À8.1°to 5.4°, dependent on the ablation powers and energy types (Fig. 11).…”
Section: Discussionmentioning
confidence: 58%
“…nos. 12,15,18,20,21,23, and 24. The analysis of variance (ANOVA) has also been performed to analyze the relative influence of selected parameters on the ablation volume attained for different experiments of Taguchi's L27 orthogonal array during FIGURE 4 Shapes of ablation volumes (corresponding to isotherm of 60 C) attained after 5 min of MWA application for different experiments of Taguchi's L27 orthogonal array MWA.…”
Section: Resultsmentioning
confidence: 99%
“…Although, in vivo animal studies and clinical trials are useful for evaluating the efficacy of any device, but numerical modeling could play a crucial role, specifically, during the design of devices for MWA; serving as a quick, convenient and inexpensive evaluation to isolate and optimize the device during prototyping . Several computational studies are available in the literature on mathematical modeling of MWA, specifically in one compartment model of the hepatic tissue . Most of these reported studies are based on axisymmetric model, with few incorporating temperature dependent parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation